Person Deixis in Debat Calon Presiden-Wakil Presiden 2019 Tahap I - Hetty Catur Ellyawati (ETERNAL (English Teaching Journal), 2019)
Person deixis is a way to point someone through pronoun, but in spesial cases, it can indicate some meaning. The writer uses deixis analysis to show how the candidates in Debat Presiden dan Wakil Presiden 2019 Tahap I use deixis to convey their goal to gain more voters. The data is taken from https://tirto.id/transkrip-lengkap-debat-perdana-pilpres-2019 which contents debates Tahap I in six segment, but using purposive random sampling, the writer only take three segments as sample. From the data analysis, it can be seen that both parties, Jokowi & Maruf and Prabowo & Sandi share the same technique to express their utterance in the Debate. They mostly used Kita as the pronoun deixis to denote theirselves and Indonesian people, then pronoun Saya, to refer to the first speaker in which is represented for the most part by Jokowi and Prabowo.